The Massacre of the Bride - van der Velden, Bastiaan (RELIEF - REVUE ÉLECTRONIQUE DE LITTÉRATURE FRANÇAISE, 2016)
The Massacre des innocents was one of Marcel Duchamp’s sources when composing Le Grand Verre. In this case, the “massacre” is more specifically a carnival attraction. On the other hand, the infanticide in Bethlehem is a subject that has been repeatedly depicted by various painters. For Alfred Jarry, a literary and theatrical author who particularly inspired Duchamp, the painting Le Massacre des innocents by Pieter Bruegel the Elder was a key piece that allowed him to demonstrate why he rejected historicizing art in both painting and theatre.